Social Reality as Legal Authenticity (Criticism of Bad Positive Laws in Legislation) - Yogi Prasetyo (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
This study aims to explain social reality as the authenticity of Indonesian law and criticism of legal positivism in the legislation. This study using a literature study research method with a legal philosophy approach. Data obtained from the results of literature studies on several scientific works related to the theme of the problem. Data analysis was performed using descriptive, evaluative methods. The results of the research show that there is an incorrect understanding of the law in society. This is because the legal system used in Indonesia still refers to the legacy of the Dutch colonialists. Law is only understood as mere legislation. Apart from that, it is not considered law, such as social realities in people's lives. Laws must be written and issued by state institutions, not norms that arise from social life in society. The law's impact is dry from the social values of society so that the law is far from the sense of justice that is expected by the community. This study is expected to provide benefits to uphold the authentic Indonesian legal sovereignty that originates from the social realities of society. So that Indonesia is free from the bad influence of the legacy of the Dutch colonial legal system because the social reality of society is the original form of Indonesian law.